PERAN NOTARIS TERHADAP PENERAPAN ASAS KEBEBASAN BERKONTRAK PADA PERJANJIAN BAKU PEMBIAYAAN KENDARAAN BERMOTOR DENGAN JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Monica Siskaniati (Universitas Islam Malang, 2022)
Financing Agreements with Fiduciary Transfer of Ownership on Vehicles generally use a Standard Agreement or commonly known as a Standard Contract. Fiduciary collateral must be registered at the Fiduciary Transfer of Ownership Registration Office to obtain a Fiduciary Transfer of Ownership Certificate. Article 15 of Act Number 42 of 1999 concerning Fiduciary Transfer of Ownership states that